2016
DOI: 10.1371/journal.pone.0149583
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy of Recognition of Chinese Multi-Character Words: Convergent Evidence from Effects of Transposable Nonwords, Lexicality, and Word Frequency

Abstract: This fMRI study aimed to identify the neural mechanisms underlying the recognition of Chinese multi-character words by partialling out the confounding effect of reaction time (RT). For this purpose, a special type of nonword—transposable nonword—was created by reversing the character orders of real words. These nonwords were included in a lexical decision task along with regular (non-transposable) nonwords and real words. Through conjunction analysis on the contrasts of transposable nonwords versus regular non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Whole-brain contrasts were thresholded at P < 0.005 and corrected for multiple comparisons to P < 0.05 (16 contiguous voxels) using AFNI’s updated 3dClustSim, a spatial clustering operation with 10 000 Monte Carlo simulations on the whole brain echo-planar imaging matrix. A threshold of P < 0.005 was reasoned to be sufficiently conservative given our interest in the regions of overlap identified in the conjunction analyses, and reducing Type II errors as a result ( Lieberman and Cunningham, 2009 ; Lin et al , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-brain contrasts were thresholded at P < 0.005 and corrected for multiple comparisons to P < 0.05 (16 contiguous voxels) using AFNI’s updated 3dClustSim, a spatial clustering operation with 10 000 Monte Carlo simulations on the whole brain echo-planar imaging matrix. A threshold of P < 0.005 was reasoned to be sufficiently conservative given our interest in the regions of overlap identified in the conjunction analyses, and reducing Type II errors as a result ( Lieberman and Cunningham, 2009 ; Lin et al , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…With neural evidence [ 52 , 53 ], this model suggests that the dorsal pathway plays a role in the early selection of features in spatial processing by identifying and selecting relevant regions in space to be passed on the ventral stream or back to early visual areas for more detailed processing [ 49 ]. Recent investigations of the TCE demonstrated the involvement of the left IPL, showing increased activation during the transposition condition [ 27 , 42 ]. In particular, Carreiras et al [ 42 ] reported greater activation in the left IPL for letter strings than for symbol and digit strings.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Carreiras et al [ 42 ] reported greater activation in the left IPL for letter strings than for symbol and digit strings. Expanding their findings into the word level, Lin et al [ 27 ] demonstrated the IPL activation with the transposed nonwords compared to the regular words in Chinese. These findings support the involvement of the dorsal pathway in early visual word recognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations